2000
DOI: 10.1111/j.1540-8175.2000.tb01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Left Ventricular Endocardial Border Delineation with an Intravenous Injection of SonoVue, a New Echocardiography Contrast Agent:

Abstract: The safety and efficacy of SonoVue (also referred to as BR1), a new contrast agent for delineating endocardial border of the left ventricle after intravenous administration, was assessed. Two hundred and eighteen patients with suspected coronary artery disease undergoing fundamental echocardiography for the assessment of left ventricle were enrolled in a prospective multicenter, single blind, cross-over study with random sequence allocation of four different doses of SonoVue. Endocardial border definition in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 19 publications
2
26
0
1
Order By: Relevance
“…Secondary generation transpulmonary contrast agents increase backscatter in an ultrasound field and opacify the left ventricular cavity. Some studies demonstrated an improvement of endocardial border delineation at rest and during stress testing after the administration of a transpulmonary contrast agent (11)(12)(13)(14). In the present study, at-rest echochardiography graded 536 of 992 (54%) myocardial segments as a score of 2 and peak DSE graded only 434 of 992 (44%) segments as a score of 2 before the intravenous bolus of SonoVue or Optison because of an invisible or barely visible left ventricular endocardial border.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Secondary generation transpulmonary contrast agents increase backscatter in an ultrasound field and opacify the left ventricular cavity. Some studies demonstrated an improvement of endocardial border delineation at rest and during stress testing after the administration of a transpulmonary contrast agent (11)(12)(13)(14). In the present study, at-rest echochardiography graded 536 of 992 (54%) myocardial segments as a score of 2 and peak DSE graded only 434 of 992 (44%) segments as a score of 2 before the intravenous bolus of SonoVue or Optison because of an invisible or barely visible left ventricular endocardial border.…”
Section: Discussionsupporting
confidence: 45%
“…The value of contrast dobutamine stress echocardiography in detecting coronary artery disease in overweight and obese patients. Can J Cardiol 2007;23 (11):885-889.…”
mentioning
confidence: 99%
“…However, echocardiographic images are sometimes of poor quality and in a recent review article high intra-and inter-observer variabilities were reported for echocardiographic LVEF assessment. 5 Left ventricular opacification (LVO) with echo contrast has been shown to improve image quality and in particular endocardial border delineation 8,9 and this may improve intraand inter-observer variability. Therefore, we conducted a post-AMI trial in which LV-EF was assessed with secondharmonic imaging (SHI) and LVO.…”
Section: Introductionmentioning
confidence: 99%
“…Sono Vue® can provide ventricular opacification and improve endocardial border definition [ 45] and Doppler signal. Moreover its utility was shown in myocardial perfusion studies [ 46,47].…”
Section: Characteristics Of Sonovue®mentioning
confidence: 99%